The image of the teacher Celestine Freinet: explication of conceptual and theoretical concepts (on the occasion of the 125th birthday) - Lyubov' A. Kochemasova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The author refers to the legacy of the outstanding French teacher, reformer, politician Celestine Freinet to reveal a special understanding of the nature and process of child development, his philosophical idea of pedagogy. The research made an attempt at a scientific search for questions of interest to a teacher involved in the study of the independent personality of students. Celestine Freinet sought to answer several important questions: Why might children want to learn? What will make them want this? Why might they lack a thirst for knowledge? The paper presents a comprehensive study of the conceptual and theoretical foundations of C. Freinet pedagogy, including an analysis of the image of a modern teacher in his heritage: past, present and future, the humanistic paradigm of education in the pedagogical concept, school self-government, moral and civic education of students as the basis of the Celestine Freinet education system and as a supporter of inculcating love for work in the process of educating the younger generation. Rethinking the historical and pedagogical heritage of C. Freinet from the standpoint of the modern development of pedagogical science and practice, the implementation of the leading ideas are the basis for further integration of conceptual humanistic views in the context of the formation of historical and pedagogical competencies of students. The article actualizes the main aspects of the dialectical unity of the continuity of traditions (past) innovations (present to the future), reflecting the process of transferring the historical and pedagogical heritage to modern educational practice. The author identifies and substantiates a number of theoretical provisions in the system of С. Freinet, implemented in modern conditions of education in the format of the international competition of research and creative works of students In the world of wise thoughts of domestic and foreign scientists and teachers.